SYNTHESIS AND CHARACTERIZATION OF Fe2O3 NANOPARTICLES USING Averrhoa bilimbi AS BIOMATERIAL CHELATING AGENT FOR NANOFLUIDS APPLICATION - Arie Hardian; Alvi Aristia Ramadhiany; Dani Gustaman Syarif; Senadi Budiman (UNIVERSITAS SEBELAS MARET (UNS), 2017)
The aim of this work was to determine the effect of calcination temperature on the characteristics of Fe2O3 nanoparticles (NPs) in sol-gel synthesis. The obtained Fe2O3 NPs was then used as material for preparation of Fe2O3-water nanofluids. Nanofluids is a mixture between basic fluid like water and 1 - 100 nm solid particles (nanoparticles). Nanoparticles of Fe2O3 have been synthesized from the local mineral Jarosite using sol-gel method by using starfruit (Averrhoa bilimbi) extracts as the chelating agent. The calcination temperature was then varied from 500 ºC to 700 ºC for 5 hours. Based on the X-Ray Diffraction (XRD) analysis, the diffraction pattern of obtained Fe2O3 was relevant with the JCPDS data No. 33-0664 for α-Fe2O3 with hexagonal crystallite system. The crystallite size (Scherrer’s Equation) of obtained α-Fe2O3 nanoparticles at calcination temperatures of 500 ºC, 600 ºC and 700 ºC was 50 nm, 48 nm and 40 nm, respectively. The Surface Area of Fe2O3 NPs at temperature of 500 ºC, 600 ºC and 700 ºC was 45.45 m2/g; 26.91 m2/g and 17.51 m2/g, respectively. Fe2O3-water nanofluids was relativly stable with zeta potential of -39.60 mV; -46.37 mV and -41.57 mV, respectively for 500 ºC, 600 ºC and 700 ºC calcination temperature. The viscosity of Fe2O3-water nanofluids was higher than the viscosity of water. The critical heat flux (CHF) value of water-Fe2O3 nanofluids was higher than the CHF water. The highest CHF value for nanofluids was obtained by using α-Fe2O3 nanoparticles with calcination temperature of 600 ºC which 34.99 % of increment compare to the base fluid (water).